2019
DOI: 10.1080/23802359.2019.1640091
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Torreya nucifera (Taxaceae) and phylogenetic analysis

Abstract: Torreya nucifera (L.) Siebold & Zucc. (Taxaceae) is a tertiary relict tree species with a distribution that is limited to South Korea and Japan. In the present study, the complete chloroplast (cp) genome of T. nucifera was sequenced and analyzed. The genome was 136,985 bp in length and contained 118 genes, including 82 protein-coding genes, 33 tRNA genes, and 4 rRNA genes. Fifteen of the genes contained a single intron, whereas ycf3 contained two introns and there were no inverted repeat sequences in the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…However, this typical structure is altered in some plant lineages. For instance, in Cupressaceae [4] and Taxaceae [5], one IR has been lost. In Pinaceae, the IR length is reduced to below 1 kb [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, this typical structure is altered in some plant lineages. For instance, in Cupressaceae [4] and Taxaceae [5], one IR has been lost. In Pinaceae, the IR length is reduced to below 1 kb [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that some ndh genes (such as ndhD and ndhH ) may have been lost randomly regardless of genome rearrangement ( Fig 9 ). The loss and pseudogenization of ndh genes are known to occur frequently in heterotrophic plants, but have also been consistently identified in gymnosperms, such as conifers [ 10 , 13 ] and Gnetales [ 71 ], and angiosperms such as Circaeasteraceae [ 72 ] and Orchidaceae [ 70 ]. Further studies are needed to assess whether the ndh genes in Corydalis spp.…”
Section: Discussionmentioning
confidence: 99%
“…Major genomic structural changes-such as gene loss, large inversions, and contraction or expansion of the IR region-are frequently reported in the plastid genomes of certain plant lineages. For example, certain conifers [9,10] and some Fabaceae plants [11] have lost one IR region. Some Pinaceae species have been shown to possess smaller IRs with a size of less than 1 kb [12,13], and some Ericaceae species exhibit a greatly reduced SSC region [14][15][16][17] due to IR extension.…”
Section: Introductionmentioning
confidence: 99%
“…The genomic content of chloroplasts is rich with valuable information, making them ideal models for research, particularly in the fields of molecular markers, barcoding identification, plant phylogenetics, evolution, and comparative genomic studies [17][18][19][20]. The chloroplast genome is recognized for its greater conservation compared to nuclear or mitochondrial genomes in terms of genetic structure, gene content, and nucleotide sequence.…”
Section: Introductionmentioning
confidence: 99%